â€œHALALâ€ AS A COMPETITIVE DISTINCTION FOR ISLAMIC HIGHER EDUCATION IN PREPARING MUSLIM MILLENIALS - Salman, Abdul Matin; Halim, Abd.; Rohman, Nur; Susilayati, Muslimah (IAIN Surakarta, 2018)
The present study aims to investigate the implementation of halal as a competitive distinction for Islamic higher education in preparing the Muslim millennials at the State Islamic Institutes. This research employed both quantitative and qualitative (mixed method) by administering questionnaires to final semester students and conducting interviews with the campus program planners. The data were descriptively analyzed by using statistical computation before being interpreted. The finding showed that 72,9% of the students had studied halal concept, 83,3% of them had known halal products from MUI labels, and 45,8% of them understood the maqasid shariah. The results of interviews revealed that the institution is continuing to prepare the establishment of halal study center by collaborating with other institutions.